STARTEGI PENGEMBANGAN PROGRAM STUDI DALAM PERSPEKTIF MANAJEMEN STRATEGIK - Mustari . (STKIP Pembangunan Indonesia Makassar, 2017)
This study aims to determine the factors with the develovment berubungan Ecocnomic Education Cooperative Studies Program at the State University of Makassar and the most appropriate strategy for development of economic education cooperative Studies Program at the State University of Makassar. This study is conducted by using a type of quantitative-qualitative approach and the research design is descriptive by using SWOT analysis. These results indicate that the position of the development strategy of economic education cooperative studies program faculty of economics, state university of makassar is located on an aggresive strategy, which means that it has a number of strenght and also have a chance so it takes SO strategy (strength-opportunity) that harness the strenght of the internal conditions for seize the opportunities that exist in external conditions.Keywords: strategy, development, management